A conceptual framework for understanding Western-centrism in transnational education in tourism. Issue 1 (2nd January 2023) - Viol, Maren; Southall, Carol
ABSTRACT: Western-centrism in tourism theory is acknowledged within the academic community. However, there is little consideration of its implications for transnational education, which might include the delivery of degrees from Western universities in non-Western contexts. This letter provides a conceptual framework that offers deeper understanding of potential issues and ways forward.